Effectiveness of an oral health education programme in primary schools in Zimbabwe after 3.5 years - Frencken JE, Borsum-Andersson K, Makoni F, Moyana F, Mwashaenyi S, (Blackwell Synergy, 2001)
Many medical and dental professionals in African nations believe that school teachers, through attendance of a short workshop, can be trained to provide oral health education. This increases the number of professionals available and is regarded as an important way forward in improving oral health.